2001
DOI: 10.1034/j.1600-0412.2001.080003262.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cervical smears secured with different instruments

Abstract: Henceforth, we believe that the use of the cervical brush and the Ayre wooden spatula increases the quantity and preservation of the cells retrieved during cervical smears compared to Acellon Combi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In addition, HPV genotype analysis revealed that the same HPV genotype(s) were detected in the endocervical specimen as were found in the vaginal scrapes, thereby giving a 100% concordance rate for both sampling procedures. The Ayre spatula used in this study as the collection device (Figure 1) gave both consistent and reproducible results [10], and was well tolerated, particularly by women who were retested. This was reminiscent of earlier reports, which documented the superiority of the Ayre spatula over other collection devices, including cotton swabs and self‐administered tampons [10,12,14].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In addition, HPV genotype analysis revealed that the same HPV genotype(s) were detected in the endocervical specimen as were found in the vaginal scrapes, thereby giving a 100% concordance rate for both sampling procedures. The Ayre spatula used in this study as the collection device (Figure 1) gave both consistent and reproducible results [10], and was well tolerated, particularly by women who were retested. This was reminiscent of earlier reports, which documented the superiority of the Ayre spatula over other collection devices, including cotton swabs and self‐administered tampons [10,12,14].…”
Section: Discussionmentioning
confidence: 85%
“…The Ayre spatula used in this study as the collection device (Figure 1) gave both consistent and reproducible results [10], and was well tolerated, particularly by women who were retested. This was reminiscent of earlier reports, which documented the superiority of the Ayre spatula over other collection devices, including cotton swabs and self‐administered tampons [10,12,14]. The use of the latter devices was often associated with variable and generally lower rates of HPV detection.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations